Optimal application of multi-agent environmental decisionmaking model in the replication and relocation of traditional villages in areas prone to geological hazards—taking wengcao village, a traditional village in Guzhang county, western Hunan as an example. Issue 1 (September 2020) - Nie, Changhong; Tang, Yuanqiang; Ou, Sanren; Chen, Yuxiang; Tang, Yuanxing; Long, Shaoqiu; Zhang, Li; Feng, Xiangzhong; Jiao, Sheng
Abstract: Wengcao Village, listed in the fourth batch of traditional villages in China, is a remote Miao village which built in a landslide-prone risk, and always at the risk of geological hazard-prone area. In order to solve the contradiction between the protection of traditional villages and the economic development of traditional villages, on the basis of environmental behavior, spatial behavior and complex theory, the author combined with the investigation. For the first time, a four-dimensional collaboration model of expert supervision, enterprise leadership, government guidance, and public participation was creatively proposed to ensure the replication and relocation of traditional villages. Aim to ensure the smooth progress of the replication and construction of traditional villages, the current popular neural network prediction model and reinforcement learning multi-agent model are combined to build a replication and construction decision model and its optimize to avoid possible future risks.